Daniel Defoe : contrarian - Merrett, Robert James (Toronto [Ont.] : University of Toronto Press, 2013)
In this study, Robert James Merrett approaches Defoe's body of work using interdisciplinary methods that recognize dialectic in his verbal creativity and cognitive awareness.
1 Contraries: Linguistic, Narrative, and Theological -- 2 Just Reflections -- 3 Serious Reflections : An Apology for Faith and Fiction -- 4 Biblical Allusions as Narrative Resources -- 5 Political Impersonations and Cultural Implications -- 6 Political Imaginings: Sacred and Profane -- 7 Marriage and Matrimony: The Dialectic of Sex and Love -- 8 Defoe's Imaginary : Narrative Inference, Figurative Expression, and Spiritual Cognition.
Includes bibliographical references (pages 361-380) and index.
English.
JSTOR
Keywords: Defoe, Daniel, -- 1661?-1731 -- Criticism and interpretation; Defoe, Daniel, -- 1661?-1731 -- Psychology; Defoe, Daniel, -- 1661?-1731; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Psychology; Criticism, interpretation, etc